Dynamic Model of The Impact of Macro Indicators and Islamic Monetary Policy Instruments on The Dual Banking System - Qothrinnada Maisuroh; Muhammad Adam (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2022)
Indonesia is the largest Muslim country with a unique monetary system that in its development tries to juxtapose two monetary systems that have different philosophies and still need to be deepened on the extent of their impact and effectiveness on the economy. The study explores the impact of macro indicators and monetary policy instruments on economic output in Indonesia. Using the time series analysis method with the Vector Error Correction Model (VECM) approach, the model shows the results that the Macro Capital Market or Stock Market indicators have a positive impact on the economy both in the short and long term. At the same time, inflation responds positively to short-term behavior but becomes economic constraints in long-term action. Meanwhile, in the Monetary policy instruments’ scope, the M1 variable consistently has positive implications both in the short and long term. In contrast, the M2 and SBIS variables give negative responses in the short time but become a driving force for the economy in the long term. Meanwhile, there is no positive correlation between Sharia, Monetary Operations with Economic Output. The research suggests focusing on innovating sharia monetary policy instruments by continuing to carry out monetary policy reforms in order to stimulate better economic conditions.